Reduplication patterns as signals of meaning in Iloko - a descriptive analysis - Albano, Fe (Racimo)
The study presents an analytical description of Iloko reduplication structures as signals of meaning on the premise that in learning a foreign language, there is a transfer of learning from the native language to the target language. Lado's CVD method of presentation is used in the making of the descriptive analysis. Two general classes and six specific types of Iloko reduplication patterns have been discovered together with twenty-three significant meanings. Likewise, Iloko reduplication patterns have shown four types of morphophonemic changes.